2021
DOI: 10.5194/aab-64-7-2021
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and phylogenetic relationship of nine sheep populations based on microsatellite markers

Abstract: Abstract. The objective of this study was to assess the genetic diversity and phylogenetic relationship of nine sheep populations, including two famous high prolific populations and seven popular mutton populations raised in China. Overall, these sheep populations in this study exhibited a rich genetic diversity. Both the expected heterozygosity and Nei's unbiased gene diversity ranged from 0.64 to 0.75, with the lowest value found in Dorset sheep (DST) and the highest in Hu sheep (HUS) and Ba Han sheep (BAS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Evolution of sheep has been studied by a number of scientists across the globe based on D-loop, ND or Cytochrome B gene as mitochondrial gene 19 . The current study revealed that mitochondrial genes with all 37 genes including 13 coding genes and rest non coding and a control region (D loop), provide a better in site for evolutionary studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evolution of sheep has been studied by a number of scientists across the globe based on D-loop, ND or Cytochrome B gene as mitochondrial gene 19 . The current study revealed that mitochondrial genes with all 37 genes including 13 coding genes and rest non coding and a control region (D loop), provide a better in site for evolutionary studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on sheep evolution and hylogenetic analysis have been studied across the globe based on either single or two mitochondrial gene, microsatellite, SNP or Y chromosome, but phylogenetic analysis through complete mitochondrial genome sequences are reported here for the first time. Molecular phylogeny for sheep have been studied in different countries as Nepal 33 , India 34,1 , China 9 , Tibetan sheep 5 , Europe 4,8 , Kenya 6 , Bangladesh 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most commonly used techniques for elucidating the genetic structure and genetic identification of different breeds of sheep is genotyping using microsatellite markers [24,25]. Microsatellites or short tandem repeats (STRs) are well-known DNA markers, which have been used in a variety of applications requiring highly polymorphic and locus-specific genetic systems-for example, in paternity testing, linkage analysis, population and evolutionary genetics, calculation of genetic distances and inbreeding rates, and detection of genetic admixture [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellite markers could use to analyze genetic diversity in sheep breeds (Gaouar et al, 2012;Liu et al, 2014;Ebrahimi et al, 2017;Xia et al, 2021), goat (Bindu et al, 2012Hussain et al, 2013;Seilsuth et al, 2016;Asroush et al, 2018), and the other domestic animals (Petrovic et al, 2018).…”
Section: Introductionmentioning
confidence: 99%